Listening to the Shepard-Risset Glissando: the Relationship between Emotional Response, Disruption of Equilibrium, and Personality - Vernooij, Eveline; Orcalli, Angelo; Fabbro, Franco; Crescentini, Cristiano (Frontiers in Psychology, 2016)
The endless scale illusion, obtained by cyclically repeating a chromatic scale made up of Shepard tones, has been used in a variety of musical works. Music psychology and neuroscience has been interested in this particular psychoacoustic phenomenon mainly for studying the cognitive processes of pitch perception involved. In the present study, we investigated the emotional states induced by the Shepard-Risset glissando, a variant of the Shepard scale. For this purpose we chose three musical stimuli: a Matlab-generated Shepard Risset glissando, Jean-Claude Risset’s Computer Suite from Little Boy, which presents a Shepard-Risset glissando integrated in the aesthetic context of a composition, and an ordinary orchestral glissando taken from the opening of Iannis Xenakis’ Metastasis. Seventy-three volunteers completed a listening experiment during which they rated their emotional response to these stimuli on a 7-point Likert scale and indicated whether they had experienced a disruption of equilibrium. Personality was also measured with the Five-Factor Model of personality traits. The results show that negative emotions were most strongly evoked during listening to each of the stimuli. We also found that the Shepard-Risset glissando illusion, both within the aesthetic context of a musical composition and on its own, was capable of evoking disruption of equilibrium, frequently leading to the associated feeling of falling. Moreover, generally for the Shepard-Risset glissando illusion, higher negative emotional ratings were given by individuals who had experienced a feeling of disturbance of equilibrium relative to those who had not had this experience. Finally, we found a complex pattern of relationships between personality and the subjective experience of the glissando. Openness to experience correlated positively with positive emotion ratings for the Computer Suite, while agreeableness correlated negatively with positive emotion ratings for the Matlab stimulus. Moreover, results indicated higher (Bonferroni-uncorrected) neuroticism for those who experienced an equilibrium disturbance relative to subjects who did not have this experience during listening to the Computer Suite. These findings suggest that musical paradoxes may be of interest not only for the insights they provide on our perceptual system, but also for the richness of the emotional experience elicited during listening.